Utvärdering av ett mikroalbuminuritest till hund - Larsson, Karin (2008)
The occurrence of small amounts of albumin in urine, microalbuminuria (MA), is used both in human- and veterinary medicine as an indicator for patients who have developing proteinuria. Proteinuria can be prerenal, renal or postrenal which is important to establish during an investigation. With conventional methods decreased renal function is not detected until 70 % of renal function is lost. The ability to detect and start a treatment earlier might reverse or slow the progression of disease.